ISCHEMIC HEART DISEASE - ETIOLOGY, CLINICAL, PATHOLOGICAL AND ANATOMIC CHANGES OF THE HEART, MODERN METHODS OF TESTING AND TREATMENT (World Bulletin of Public Health, 2022)
It is known that there is a serious epidemiological situation in the cardiovascular system around the world. Cardiovascular disease is one of the leading causes of death in the world. According to the World Health Organization in 2016, 17.6 million people died of cardiovascular disease in 2016, accounting for 31% of world deaths. If 100% of deaths due to cardiovascular diseases are considered, 52.5% of them are due to angina pectoris, heart attack. According to the Centers for Disease Control and Prevention in 2019, approximately 18.2 million American adults are diagnosed with coronary artery disease and 805,000 Americans have a heart attack each year. The urgency of this problem for health, their prevalence, high mortality and disability rates, are associated with socio-economic losses affecting the country's labor potential. One of the most common types of cardiovascular disease today is angina pectoris.